Simulation of Working Processes in the Water-Tube Boiler Furnace with the Purpose of Reducing Emissions of Nitrogen Oxides - Redko A.A.; Davidenko A.V.; Pavlovskiy S.V.; Kulikova N.V.; Pavlovskaya A.A.; Redko I.A. (Problems of the Regional Energetics)
A significant number of domestic and industrial boilers are in operation in Ukraine. Nitrogen oxides are the most dangerous among all combustion products that pollute the atmosphere, therefore, one should take some measures for decreasing the formation of nitrogen oxides during combustion. The studies were carried out at the boilers of low power (100 kW) with a tubular radiator and an open end. The studies in the furnaces of industrial steam boilers having a tubular radiator with a closed end have not been done. The numerical study results of the gaseous fuel combustion processes in the furnace of a DE-10/14 steam water-tube boiler are presented. The fuel-air mixture is formed by premixing the 15% part of the air with a primary burner twist factor n=2.4 and a secondary burner twist factor n=1.6, and an air excess factor αв=10. As a result of the studies, the temperature and velocity distributions of gases in the combustion chamber, the density of heat flows on the screen tubular surfaces, and the concentrations of the combustion components were determined. Flue gas recirculation in the volume of 80-100% is provided, and the reversible movement of combustion products towards the combustion front provides a reduction in the concentration of nitrogen oxides up to 123-125 mg/m3 at the furnace outlet. Disadvantages are the following: the formation of stagnant zones near the end of the secondary radiator. The optimum diameter of the tubular radiator equals to two burners diameters and tubular radiator is located at a distance of one meter from the burner cutoff.